Incidental Finding of Bilateral Ovarian Adrenal Rest Tumor in a Patient With Congenital Adrenal Hyperplasia: A Case Report and Brief Review. (April 2021) - Bouzidi, Lobna; Triki, Meriam; Charfi, Slim; Ameur, Hana Ben; Dhaou, Mahdi Ben; Bouaziz, Touraya; Boudawara, Tahya
Ovarian adrenal rest tumors (OART) are tumors that develop in females with congenital adrenal hyperplasia (CAH). In contrast to their counterpart in testicles, they are exceptional and few cases have been reported in the literature. In this report, we present clinicopathological findings of a female patient with CAH due to 21-hydroxylase deficiency who was incidentally diagnosed with OART with a review of the literature. The 14-year-old patient, who was raised as a boy, developed a virilizing syndrome with high testosterone levels that were attributed to non adherence to her replacement corticosteroid therapy. She consulted for sex reassignment surgery. Pelvic ultrasound was normal. She underwent hysterectomy and bilateral adnexectomy. No abnormalities were noticed during the operation. Grossly, both ovaries were variegated with well circumscribed and lobulated, brownish-yellow nodules. Histologically, the nodules were composed of nests of large polygonal cells with centrally located nuclei and prominent nucleoli. There was mild atypia and no crystals of Reinke. Thus, the findings of the histopathological examination were consistent with bilateral OART. Histological differential diagnosis of OART can be challenging particularly with leydig cell tumor, stromal luteoma and steroid cell tumors, not otherwise specified. OART must be considered in women with CAH and persistent virilizing symptoms despite negative imaging results.